Effects of Co-substrate Concentrations on the Anaerobic Co-Digestion of Common Reed and Cow Dung - Van Tran, Giang; Unpaprom, Yuwalee; Ramaraj, Rameshprabu (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2019)
The biochemical methane potentials for common reed (Phragmites australis) and cow dung from northern Thailand, Chiang Mai city were investigated. This study aims to evaluate optimal parameters for the substrate of common reed and cow dung with different ratios (i.e. 1:1, 2:1 and 1:2) for improving the quality of methane content and biogas production. The effect of the co-substrate mixture was carried out in a batch reactor operated under room temperature and hydraulic retention time (HRT) of 45 days. The experiments were conducted in the fermenter with a working volume of 2.5 L and a total volume of 3L. The substrate was containing 15% of total solids (TS) and fermentation at initial pH 7. Biodegradation of substrate stated that chemical oxidation demand (COD) removal was 52.38%, the utilization of volatile solid was 75.46%. The results were achieved at ratio 2:1 (common reed and cow dung) reached the highest methane content and total biogas yield are 70% and 20,015 ml, respectively. Consequently, the results of this study suggested that mixing ratios of influence on the fermentation process and monitoring parameters were significant for further scale up or large-scale design of enriched methane content and biogas production.